Effect of Interface Strength on Elastic and Toughness Properties of Graphene-Reinforced Si3N4 Nanocomposites - Aslan, Betül; Bayrak, Osman (My University, 2025)
Silicon nitride is used in advanced engineering applications. Its toughness can be improved when they are reinforced with nanoparticles, such as graphene. Although toughness improvement is relatively more achievable with the reinforcement, elastic properties of nanocomposites are generally inferior to those of monolithic ceramics. Experimental works give rich insight into the mechanical characteristics of graphene-Si3N4 nanocomposites. However, there is no consensus yet in literature on why Young’s modulus decreases upon addition of graphene into Si3N4 nanocomposites. In this study, we aimed to reveal the reason behind the deterioration of the Young’s modulus. We created and verified finite element models based on the microstructural and mechanical data provided in literature. Different void and interfacial interaction properties were tested on the models. Results revealed that graphene does not act like voids within the matrix. It rather induces randomly dispersed porosities within the interfaces. Toughness of nanocomposites improved with increase of interfacial strength. However, interfacial strength did not directly affect Young’s modulus of nanocomposites. Following the inducing of porosities within the interfaces in finite element models, it was observed that secant modulus decreased. This finding implies that optimizing porosity distribution via contact discontinuities can help achieve approximating elastic properties of graphene-Si3N4 nanocomposite models. Findings of this study will contribute to future research on nanocomposites, including fracture behavior modeling, and toughness mechanisms
Keywords: Microstructure; Mechanical Properties; Graphene; Si3N4; Interface; Finite Element Modeling